2020
DOI: 10.1097/md.0000000000019124
|View full text |Cite
|
Sign up to set email alerts
|

The association between smartphone addiction and thumb/wrist pain

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 27 publications
(20 reference statements)
1
52
1
12
Order By: Relevance
“…Furthermore, our results for hand grip and pinch strength may be attributed to the fact that 75% of participants reported using their smartphone with the dominant hand and 25% with both hands in the current study. However, another study showed some correlation between hand grip and smartphone usage duration [ 10 , 24 , 25 ]. This might be because we did not ask the participants to use their smartphones during the period when we collected the data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results for hand grip and pinch strength may be attributed to the fact that 75% of participants reported using their smartphone with the dominant hand and 25% with both hands in the current study. However, another study showed some correlation between hand grip and smartphone usage duration [ 10 , 24 , 25 ]. This might be because we did not ask the participants to use their smartphones during the period when we collected the data.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent studies have shown a clear relation between texting with a phone and De Quervain's tenosynovitis. [5][6][7] Our child was also using mobile phone for about 8 hours a day for online classes, games and texting. Only very few pediatric cases of De Quervain tenosynovitis were reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically highly significant (X 2 =10.820; p<0.0001) association were also found between Finkelstein status and the mobile size in the collegiate students studied (Table 1). (Baabdullah, 2020). Sustained and gripping and repetitive movements with the thumb and fingers have all been identified as risk factors which may lead to disorders of the thumb and thumb musculature in the forearm.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%